A kingdom of dreams - McNaught, Judith; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1989)
Abducted from her covent school, headstrong Scottish beauty Jennifer Merrick does not easily surrender to Royce Westmoreland, Duke of Claymore.
Keywords: Aristocracy (Social class) -- England -- Fiction; Man-woman relationships -- Fiction; Scotland -- Fiction; Romantic suspense fiction; Romantic suspense fiction; Historical fiction; Love stories